ANALISIS DAN DESAIN RANTAI PASOK KAKAO BERBASIS BLOCKCHAIN - Dian Ardifah Iswari; Yandra Arkeman; Muslich Muslich (Universitas Merdeka Madiun, 2020)
Abstractâ€” The supply chain in the 4.0 era wanted consumers to be closer to producers. Problems that occur in the supply chain are supply chain information flow is still long, there is no transparency, marketing coverage is less extensive, and documentation of activities is not good. The purpose of this study is to analyze the condition of the Kelompok Tani X cocoa supply chain and to identify the attributes of the blockchain based group cocoa supply chain farmers. The method used is the System Development Life Cycle (SDLC) and Unified Modelling Languange. The results obtained are that the supply chain information flow in the X farmer group is still overlapping, and has not been systematic. Actors consist of farmers, farmer leaders, processing factories (Kelompok Tani X), and retailers. Activities that occur are signing up, logging in, filling content, transactions, shipping, validation, and returning goods. The conclusion is the supply chain activities of the Kelompok Tani X have not been documented. The blockchain system that is designed is adjusted to the situation, so it is expected to be able to make the administration and documentation system better. Â Keywordsâ€”: Agroindustry 4.0; supply chain; system development life cycle; transparency; unified modelling languange.